Mechanisms for Building Empathy and Non-Violent Communication as a Factor in Bullying Prevention - Yerkinbekova, Meirimgul; Kulanova, Sandugash; Аплашова, Арна (Pedagogy and Psychology, 2025)
The article explores the role of empathy and non-violent communication as effective tools for preventing bullying in the educational environment. Key theoretical perspectives on these phenomena and their relation to school bullying are examined. Methodology and Methods. To test the proposed hypothesis, a combination of qualitative and quantitative methods was applied, including testing, focus group interviews, surveys, and a pedagogical experiment involving control and experimental groups. Results. The analysis revealed that the level of empathy tends to increase with age, while students who experienced bullying demonstrate lower communicative competence, reduced self-esteem, and inadequate self-reflection. A significant correlation was found between empathy, communication skills, and the tendency to adopt aggressive behavior patterns. The pedagogical experiment confirmed the effectiveness of the proposed mechanisms: in the experimental group, the frequency of bullying decreased, and higher levels of empathy and non-violent communication skills were observed. Scientific novelty. For the first time, the study substantiates the complex role of empathy and non violent communication as interrelated factors in bullying prevention. Practical significance. The findings can be applied in educational programs aimed at developing non-violent interaction, enhancing psychological resilience, and fostering a safer and healthier school climate.